Functional health and cognitive impairment: insights from elderly residents in old-age homes in Delhi - M., Sreelakshmi; Mahapathro, Meerambika (International Journal Of Community Medicine And Public Health, 2024)
Background: The study aims to determine the relationship between functional health and cognitive impairment in elderly residents of old-age homes in Delhi. Methods: A descriptive cross-sectional study was conducted among 121 elderly residents from 6 selected old age homes in Delhi. Interviews were conducted using Katz ADL, Lawton IADL, and Mini-cog tools. Results: The study found that 3.3% of the study population had one ADL disability, 10.7% had 2 or more ADL disability, 18% of the respondents had one IADL disability, 47% with 2 or more IADL disability, and 57% of the residents who participated in the study were found to have a cognitive impairment. A significant association was found between ADL and IADL to self-rating of health and also, in addition to that, IADL is seen higher with increasing age, cognitive impairment, and those with less interest in working. Cognitive impairment was found more in females, with increasing age, those with lesser education, those with no income, no family contact, no emotional support, and those with no interest in working. No significant association was found between cognitive impairment and ADL in this study. Conclusions: This research focuses on identifying modifiable factors that can improve the well-being of elderly residents in old age homes, aiming to enhance geriatric care strategies. Regular cognitive assessments, along with tailored interventions, are essential to support both cognitive and functional health. Creating a supportive environment through social engagement and personalized care can help mitigate cognitive decline, improving overall quality of life.